Do small changes in rotation affect measurements of lower extremity limb alignment? - Amir A. Jamali; John P. Meehan; Nathan M. Moroski; Matthew J. Anderson; Ramit Lamba; Carol Parise (Journal of Orthopaedic Surgery and Research, 2017)
Abstract Background The alignment of the lower extremity has important implications in the development of knee arthritis. The effect of incremental rotations of the limb on common parameters of alignment has not been studied. The purpose of the study was to (1) determine the standardized neutral position measurements of alignment and (2) determine the effect of rotation on commonly used measurements of alignment. Methods Eighty-seven full length CT angiography studies (49 males and 38 females, average age 66 years old) were included. Three-dimensional models were created using a rendering software program and placed on a virtual plane. An image of the extremity was obtained. Thirty scans were randomly selected, and those models were rotated in 3° intervals around the longitudinal axis and additional images were obtained. Results In the neutral position, the mechanical lateral distal femoral articular angle (mLDFA) was 85.6 ± 2.3°, medial proximal tibial angle (MPTA) was 86.1 ± 2.8°, and mechanical tibiofemoral angle (mTFA) was −0.7 ± 3.1°. Females had a more valgus alignment with a mTFA of 0.5 ± 2.9° while males had a more varus alignment with a mTFA of −1.7 ± 2.9°. The anatomic tibiofemoral angle (aTFA) was 4.8 ± 2.6°, the anatomic lateral distal femoral angle (aLDFA) measured 80.2 ± 2.2°, and the anatomical-mechanical angle (AMA) was 5.4 ± 0.7°. The prevalence of constitutional varus was 18%. The effect of rotation on the rotated scans led to statistically significant differences relative to the 0° measurement for all measurements. These effects may be small, and their clinical importance is unknown. Conclusions This study provides new information on standardized measures of lower extremity alignment and the relationship between discreet axial rotations of the entire lower extremity and these parameters.